Trimetazidine restores the positive adaptation to exercise training by mitigating statin‐induced skeletal muscle injury. Issue 1 (19th November 2017) - Song, Ming; Chen, Fang‐fang; Li, Yi‐hui; Zhang, Lei; Wang, Feng; Qin, Ran‐ran; Wang, Zhi‐hao; Zhong, Ming; Tang, Meng‐xiong; Zhang, Wei; Han, Lu
Abstract: Background: Exercise rehabilitation is demonstrated to improve the prognosis of patients with coronary heart disease (CHD). Statins, as the key medicine to lower cholesterol in CHD, result in skeletal muscle injury and impair exercise training adaptation. Energy metabolism dysfunction is identified as the potential mechanism underlying statin‐induced skeletal muscle injury. In this study, we investigated the effects of the metabolic modulator trimetazidine on skeletal muscle energy metabolism and statin‐associated exercise intolerance. Methods: High‐fat fed apolipoprotein E knockout (ApoE −/− ) mice were given aerobic exercise and administrated simvastatin, trimetazidine, or simvastatin plus trimetazidine by gavage. Exercise capacity was evaluated at the end of the treatment by hanging grid test, forelimb grip strength, and running tolerance test. Plasma glucose, lipid, and creatine kinase concentrations were measured at the end of the treatment. After sacrifice, gastrocnemii were stored for assessment of muscle morphology and fibre type. Energy metabolism was estimated by plasma lactic acid concentration, ragged red fibres, and glycogen stores. Activities of mitochondrial complex III, citrate synthase activity, and membrane potential were measured to assess mitochondrial function. Oxidative stress was also evaluated by superoxide in mitochondria, superoxide dismutase activity, and glutathione redox state. Results: In high‐fat fed ApoE −/− mice, exercise training had no effect on lipid concentrations. Lower lipid concentrations with increased creatine kinase were observed with additional simvastatin treatment. Exercise capacity increased significantly in response to exercise training alone but was blunted by the addition of simvastatin. Similarly, cross‐sectional area of muscle fibres and the proportion of slow‐twitch fibres increased in the exercise group but decreased in the simvastatin plus exercise group. Additionally, simvastatin increased centronucleated fibres and induced energy metabolism dysfunction by inhibiting complex III activity and thus promoted oxidative stress in gastrocnemius. We demonstrated that trimetazidine could reverse simvastatin‐induced exercise intolerance and muscle damages. We also found the ability of trimetazidine in restoration of muscle fibre hypertrophy and facilitating fast‐to‐slow type shift. The energy metabolism dysfunction and oxidative stress in gastrocnemii were rescued by trimetazidine. Conclusions: Trimetazidine alleviated statin‐related skeletal muscle injury by restoration of oxidative phenotype and increasing fibre cross‐sectional areas in response to exercise training. Correspondingly, the exercise training adaptation were improved in high‐fat fed ApoE −/− mice. Moreover, trimetazidine is able to exert its positive effects without affecting the beneficial lipid‐lowering properties of the statins. Thus, trimetazidine could be prescribed to remedy the undesirable statins‐induced exercise intolerance during cardiac rehabilitation in patients with CHD.